Zooplankton assemblages in Melaban and Sebayor River, Sarawak - Nurma Sarah, Binti Jaafar (Universiti Malaysia Sarawak, UNIMAS, 2012)
A study was carried out on the zooplankton assemblages in Melaban and Sebayor Rivers to determine the composition, species diversity, abundance, distribution and selected water physico-chemical parameters. Zooplankton and water samples were collected from six sampling stations on 7 December 2011 and 13 February 2012. Zooplankton and water samples be analysed using standard methods in the interpreting information about zooplankton assemblages and it relationship to the water quality parameters. There 19 genera belonging to five class were identified during this study was conducted. The group of Copepoda was dominated the zooplankton communities which made up of 53% of total abundance. Zooplankton abundance in these rivers followed by the order: Copepoda > Anostraca > Rotifera> Cladocera. A dominant genus identified in this study was Diaptomus which is represent 39.57% of total amount of zooplankton communities. In comparison the zooplankton was recorded much higher during first sampling (445 individuals) than to second sampling (148 individuals). Species diversity values ranges from 1.27 to 2.62. Temperature, pH, salinity, dissolved oxygen, total suspended solid, biological oxygen demand and nutrient were probably water quality parameters which were found to influence zooplankton composition in Melaban and Sebayor River.